Spontaneous splenic rupture associated with Q fever and portal hypertension: A case report - Cecil Mustafiz; Cecil Mustafiz; Deloshaan Subhaharan; Deloshaan Subhaharan; Daniel Chorley; Tariq Masood (Frontiers in Medicine)
Spontaneous splenic rupture (SSR) is an exceptionally rare and life-threatening condition, with its pathophysiology remaining poorly understood. This report describes the first documented case of SSR in a patient with Q fever infection and underlying liver cirrhosis with portal hypertension. The patient was a man in his late 30 s who presented with severe abdominal pain, vomiting and hypovolemic shock who required emergency splenectomy due to unstable splenic hemorrhage. Post-operatively, a diagnosis of Q fever was confirmed through serological testing. To date, there has only been six cases describing splenic rupture precipitated by Q fever, and none in the context of concurrent portal hypertension. Conversely, portal hypertension is an independent risk factor for splenic complications including splenomegaly and hypersplenism. This case underlines the critical need to consider rare etiologies, offers valuable insights into the pathogenesis of SSR, and emphasizes the importance of early recognition and multidisciplinary management. Moreover, a proposed algorithm for the diagnosis and management of SSR has been included for clinicians who face similar complex presentations.